1991
DOI: 10.1177/074823379100700303
|View full text |Cite
|
Sign up to set email alerts
|

Benzo-a-Pyrene: Environmental Partitioning and Human Exposure

Abstract: A multimedia transport model was used to evaluate the environmental partitioning of benzo-a-pyrene (BaP). Measured and predicted environmental concentrations were used to estimate the accumulation of BaP in the food chain and the subsequent extent of human exposure from inhalation and ingestion. Results show that BaP partitions mainly into soil (82%) and sediment (17%) and that the food chain is the dominant pathway of human exposure, accounting for about 97% of the total daily intake of BaP. Inhalation and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
89
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(89 citation statements)
references
References 36 publications
0
89
0
Order By: Relevance
“…In contrast, nonmeat items contained up to 0.5 ng/g [Kazerouni et al, 2001]. The daily dietary intake of B[a]P has been estimated to range from 120 to 2800 ng/day [Hattemer-Frey et al, 1991], with average values approximating 600 ng/day [Scherer et al, 2000]. Catabolism of PAHs can generate reactive diol-epoxides, which have been shown to form stable DNA adducts at mutational hotspots in the p53 and Harvey-ras genes, disrupt transcription, and the binding affinity of Sp1 and E2F transcription heterodimers to DNA [MacLeod et al, 1995;Denissenko et al, 1996;Butler et al, 1997].…”
Section: Pahs As Exogenous Risk Factors In Carcinogenesismentioning
confidence: 99%
“…In contrast, nonmeat items contained up to 0.5 ng/g [Kazerouni et al, 2001]. The daily dietary intake of B[a]P has been estimated to range from 120 to 2800 ng/day [Hattemer-Frey et al, 1991], with average values approximating 600 ng/day [Scherer et al, 2000]. Catabolism of PAHs can generate reactive diol-epoxides, which have been shown to form stable DNA adducts at mutational hotspots in the p53 and Harvey-ras genes, disrupt transcription, and the binding affinity of Sp1 and E2F transcription heterodimers to DNA [MacLeod et al, 1995;Denissenko et al, 1996;Butler et al, 1997].…”
Section: Pahs As Exogenous Risk Factors In Carcinogenesismentioning
confidence: 99%
“…Population studies detected the accumulation of TCDD in breast milk (13,14), suggesting that this agent may reach breast tissue and be a risk factor in mammary neoplasia. Another class of environmental pollutants is polycyclic aromatic hydrocarbons (PAH), including the prototypical carcinogen benzo(a)pyrene [B(a)P], which is found in cigarette smoke and cooked meat (15). Diet contributes average values of 600 ng/d of B(a)P (16).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that vegetation can accumulate both gas-phase and particle bound SVOCs from the atmosphere providing a means for air pollutants to enter the foodchain (Hattemer-Frey and Travis, 1991;Jones et al, 1991;EPA, 1994;McLachlan, 1996;Welsch-Pausch and McLachlan, 1998;EPA, 1998d;Bohme et al, 1999;Kaupp et al, 2000). Plants also accumulate pollutants from the soil but the importance of the soil-to-plant pathway for atmospheric pollutants is generally negligible (Welsch-Pausch et al, 1995).…”
Section: Introductionmentioning
confidence: 99%